Statin-associated anti-HMGCR immune-mediated necrotizing myopathy with dermatomyositis-like features: A case report. (December 2020) - Lim, Darosa; Landon-Cardinal, Océane; Ellezam, Benjamin; Belisle, Annie; Genois, Annie; Sirois, Jennifer; Bourré-Tessier, Josiane
Anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) immune-mediated necrotizing myopathy is a subtype of idiopathic inflammatory myopathy which may be associated with statin exposure. It presents with severe proximal muscle weakness, high creatine kinase levels and muscle fiber necrosis. Treatment with intravenous immunoglobulins and immunosuppressants is often necessary. This entity is not commonly known among dermatologists as there are usually no extramuscular manifestations. We report a rare case of statin-associated anti-HMGCR immune-mediated necrotizing myopathy with dermatomyositis-like cutaneous features. The possibility of anti-HMGCR immune-mediated necrotizing myopathy should be considered in patients with cutaneous dermatomyositis-like features associated with severe proximal muscle weakness, highly elevated creatine kinase levels and possible statin exposure. This indicates the importance of muscle biopsy and specific autoantibody testing for accurate diagnosis, as well as significant therapeutic implications.